1988
DOI: 10.1523/jneurosci.08-02-00580.1988
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of ganglioside antigens recognized by the JONES antibody

Abstract: The JONES monoclonal antibody has been immunocytochemically associated with regions of the developing rat brain where cell and axon migrations are occurring (Mendez-Otero et al., 1986, 1988). In the present study the antigens recognized by the JONES antibody were analyzed in a variety of brain regions and at developmental ages selected to correspond to the preceding immunocytochemical observations. In accordance with earlier results from retina, JONES binding could not be detected in SDS gels from developing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…This O-acetylation of Sia is a common modification found in mammalian cell surface sialoglycoconjugates and can also be present on free Sias in the cytosol (15,16). One example of a well characterized O-acetylated sialoglycoconjugate is 9(7)-Oacetylated-G D3 and structurally related disialogangliosides, which show developmentally regulated expression and gradient patterns for its staining with monospecific antibodies in the developing brain (17,18). Specific antibodies showed that the expression of 9-O-acetylated G D3 appears to be independently regulated from that of the parental molecule, G D3 (18), and occurs on the migrating neural cells (19).…”
mentioning
confidence: 99%
“…This O-acetylation of Sia is a common modification found in mammalian cell surface sialoglycoconjugates and can also be present on free Sias in the cytosol (15,16). One example of a well characterized O-acetylated sialoglycoconjugate is 9(7)-Oacetylated-G D3 and structurally related disialogangliosides, which show developmentally regulated expression and gradient patterns for its staining with monospecific antibodies in the developing brain (17,18). Specific antibodies showed that the expression of 9-O-acetylated G D3 appears to be independently regulated from that of the parental molecule, G D3 (18), and occurs on the migrating neural cells (19).…”
mentioning
confidence: 99%
“…The particular epitope recognized by the Jones mAb depends upon the acetyl group at position 9 of sialic acid and the immunoreactivity is abolished by mild base treatment since this treatment converts 9-O-acetyl GD3 to GD3 that is not recognized by the Jones mAb (13,30,31). This antigen is abundant in the nervous system and in tumor cells derived from the neural crest, and is absent in most of the other tissues examined (29). However, the same epitope was described in the immune system and was designated CD60b (32).…”
Section: Gangliosides and Neuronal Motilitymentioning
confidence: 82%
“…In our initial studies we have shown that the pattern of staining with this antibody in the developing rat nervous system correlates temporally and spatially with neuronal migration and neurite outgrowth (28,29). The biochemical characterization of the antigen revealed that this mAb recognizes a ganglioside that migrates between GM1 and GM2 ganglioside standards.…”
Section: Gangliosides and Neuronal Motilitymentioning
confidence: 96%
See 2 more Smart Citations